Economic benefits associated with beta blocker persistence in the treatment of hypertension: a retrospective database analysis. (17th February 2015) - Chen, Stephanie; Swallow, Elyse; Li, Nanxin; Faust, Elizabeth; Kelley, Caroline; Xie, Jipan; Wu, Eric
Abstract: Objectives: To assess the association between medical costs and persistence with beta blockers among hypertensive patients, and to quantify persistence related medical cost differences with nebivolol, which is associated with improved tolerability, versus other beta blockers. Methods: Adults who initiated hypertension treatment with a beta blocker were identified from the MarketScan* claims database (2008-2012). Patients were classified based on their first beta blocker use: nebivolol, atenolol, carvedilol, metoprolol, and other beta blockers. Patients with compelling indications for atenolol, carvedilol or metoprolol (acute coronary syndrome and congestive heart failure) were excluded. Patients enrolled in health maintenance organization or capitated point of service insurance plans were also excluded. Persistence was defined as continuous use of the index drug (<60 day gap). The average effect of persistence on medical costs (2012 USD) was estimated using generalized linear models (GLMs). Regression estimates were used to predict medical cost differences associated with persistence between nebivolol and the other cohorts. Results: A total of 587, 424 hypertensive patients met the inclusion criteria. Each additional month of persistence with any one beta blocker was associated with 152.51 in all-cause medical cost savings; continuous treatment for 1 year was associated with 1585.98 in all-cause medical cost savings. Patients treated with nebivolol had longer persistence during the 1 year study period (median: 315 days) than all other beta blockers (median: 156–292 days). Longer persistence with nebivolol translated into 305.74 all-cause medical cost savings relative to all other beta blockers. Limitations: The results may not be generalizable to hypertensive patients with acute coronary syndrome or congestive heart failure. Conclusions: Longer persistence with beta blockers for the treatment of hypertension was associated with lower medical costs. There may be greater cost savings due to better persistence with nebivolol than other beta blockers.